ТРАНСЦЕНДЕНТНОЕ ПРОСТРАНСТВО ГЕНДЕРА - Volodymyr V. Khmel; O. M. Korkh (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
This paper aims to analyze the basic principles of gender philosophy applying methodological tools of communicative pragmatics; to demonstrate how gender construct can provide gender humanism formation as one of the ideals of democratic society; to specify gender glossary terms such as “gender democracy”, “gender equality” and “gender justice”. Methodology. In order to investigate a theoretical framework in feminist philosophy, methodological tools of communicative pragmatics and discursive ethics that were elaborated by modern German philosophers J. Habermas, K.-O. Apel for analyzing ethical gender principles and their legitimation ways have been used in this research. Scientific novelty. Based on methodological differences in concepts of J. Habermas and K.-O. Apel, two opposite approaches to gender concept analysis – rational and pragmatic (Habermas) and transcendental conceptual (K.-O. Apel) have been found out. The article helps to specify the framework of categories and concepts. According to the legitimation way of gender ethical theory it was discovered that such notions as “gender democracy”, “gender equality” and “gender justice” do not have the same meanings. According to the analysis of communicative action program and consensus, the “gender equality” concept by Habermas is an artificial social construct that is methodologically grounded in cognitivism and diminishes the possibilities of gender values legitimation. According to K.-O. Apel, the concept of “gender justice” is based on transcendental moral and ethical sense of opposite genders unity and does not discharge unequal distribution of responsibilities and any invasion as well as represents certain extent of their difference. Conclusions. Fast growing gender changes in the society face ageold drawbacks of moral and spiritual principles of communities, taking into account social and cultural, national and gender identity. Thorough understanding of various approaches to feminism philosophy leads more to complementarity of male and female principles of humanity with further acceptance of gender roles that reflect more complicated panorama of spiritual life.